2015
DOI: 10.5152/tjar.2014.83435
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis Due to Hypertriglyceridaemia in Pregnancy

Abstract: Gebelik sırasında hypertrigliseridemiye bağlı akut pankreatit nadir fakat hem anne hem de bebek için ölümcül sonuçlara neden olabilen ciddi klinik bir tablodur. Otuz yedi yaşında 31 haftalık familial hypertrigliseridemi ve diabetes mellitusu olan gebede akut pankreatit gelişti. İntrauterin bebek ölümü gelişen hastanın gebeliği sonlandırıldı. Tedavide insülin, octreotidin yanısıra "double membrane filtration" ile plasmaferez uygulanarak trigliseritlerin hızla düşürülmesi sağlandı. Trigliserid düzeyi 24 saat son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Inflammatory mediators damage alveoli and cause respiratory failure, which is the most common organ failure associated with SAP. 25 The occurrence of respiratory failure was also observed in the current study. In the group that had an admission TG of over 11.2 mmol/L, the incidence of respiratory failure was as high as 38.8% (Table 5), which was much higher than the cases with TG lower than 11.2 mmol/L (P<0.05).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Inflammatory mediators damage alveoli and cause respiratory failure, which is the most common organ failure associated with SAP. 25 The occurrence of respiratory failure was also observed in the current study. In the group that had an admission TG of over 11.2 mmol/L, the incidence of respiratory failure was as high as 38.8% (Table 5), which was much higher than the cases with TG lower than 11.2 mmol/L (P<0.05).…”
Section: Discussionsupporting
confidence: 78%
“…Plasma exchange is also effective to reduce blood lipid levels urgently. 25,33 Several studies have confirmed that plasma exchange can quickly eliminate harmful cytokines and inflammatory mediators in the circulation to significantly improve clinical symptoms. 33,34 There is no large-scale study of plasma exchange in acute pancreatitis patients with hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, TG was hydrolyzed by pancreatic lipase to excess free fatty acids (FFA), which seriously damaged acinar cells and pancreatic capillary endothelium, leading to severe self-digestion of the pancreas and activation of in ammatory cells. [29] Additional, TC can lead to in ammatory responses, lysosome damage, and pro-in ammatory cytokine secretion. [30] In particular, it promoted the toll-like receptors signal enhancement, the progress in AP played a signi cant proin ammatory role.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…[12] Afterwards, a great deal of FFAs in ltrate into the pancreatic cells and the acidic environment accelerates the activation of trypsinogen, which leads to severe self-digestion of pancreas and activation of in ammatory cells. [42] Owing to the cascade reaction of various in ammatory mediators, intensive systemic in ammatory response is marked in AP. And increased in ltration of in ammatory cells that observed in multiple organs according to other reports provide the additional evidence of our hypothesis.…”
Section: Discussionmentioning
confidence: 99%